Massive Open Online Courses: learning from our learners / Tan Bee Hoon - Tan, Bee Hoon (UiTM Press, 2016)
A Massive Open Online Course (MOOC) is an emerging model of delivering learning content online via video-recording interspersed with quizzes and interaction through social media to virtually anyone usually for free. Its enrollment is usually massive, and the massiveness can be attributed to the reputation of the course professor and/or the university. A typical MOOC can be scheduled for live webcast or accessed asynchronously, involving activities such as watching lecture videos, participating in discussion forums, and working or commenting on assignments. As the MOOC instructional model was new, this study was conducted to find out how a class of 15 undergraduates of a Malaysian public university responded to learning from a five week MOOC on academic writing in English. The aim was to investigate if they encountered any challenges while learning from their very first MOOC, and also the instructional activities or features that motivated or demotivated them. Such qualitative data were collected from the students' reflection essays. The results highlighted some important issues of the MOOC pedagogy including the feasibility of the key features, course format and evaluation processes. The findings should provide useful feedback to instructors who plan to design or adopt a MOOC for instructional purposes across disciplines.